Java programming interviews exposed / Noel Markham - Markham, Noel
Chapter 5: Data Structures; Lists; Trees; Maps; Sets; Summary; Chapter 6: Design Patterns; Investigating Example Patterns; Commonly Used Patterns; Summary; Chapter 7: Implementing Popular Interview Algorithms; Implementing FizzBuzz; Demonstrating the Fibonacci Sequence; Demonstrating Factorials; Implementing Library Functionality; Using Generics; Summary; Part II: Core Java; Chapter 8: Java Basics; The Primitive